ANGKA KEJADIAN PENYEBAB KEMATIAN MENDADAK DI INSTALASI KEDOKTERAN FORENSIK DAN MEDIKOLEGAL RSUD DR. PIRNGADI MEDAN TAHUN 2013-2015 - Ismurrizal Ismurrizal (Universitas Muhammadiyah Sumatera Utara, 2018)
Sudden death is not necessarily a sudden process actually even sudden death is an end of a disease process that has been owned by the victims of sudden death. The incidences of sudden death increases with age and sudden death is more common in men than women. To determine the cause of sudden death have to do an autopsy examination which includes external and internal examination for a causal relationship between abnormalities were found with disease deaths caused by cardiovascular system, respiratory system, gastrointestinal system and genitourinary system. The purpose of this study was to determine the incidence of sudden death in installation of forensic medicine and medicolegal RSUD Dr. Pirngadi Medan in 2013-2015. The type of research is descriptive research with cross sectional design. The sampling used the total sampling technique, where as many as 40 cases used as a sample. The research results obtained by the number of sudden death by age, most are early elderly group age 45-65 years old as many as 12 (30%) and the number of sudden death by gender are 38 men (95%) and 2 women (5%). While the causes of sudden death due to respiratory system as 27 people (67,5%), due to cardiovascular system as 8 people (20%), due to gastrointestinal system as 4 people (10%) and due to genitourinary system as 1 person (2,5%).The results of this study concluded that the incidence of sudden death causes in installation of forensic medicine and medicolegal RSUD Dr. PirngadiMedan by the number of sudden death by age, most are early elderly group age 45-65 years old.While based on gender the most are men. And sudden death mostly caused by respiratory system diseases. Keywords : Sudden Death, Cause, RSUD Dr. Pirngadi Medan